1996
DOI: 10.3354/dao024025
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and prophylactic measures for winter saprolegniosis in channel catfish

Abstract: LVlnter s a p r o l e g n~o s~s In channel c a t f~s h Ictalurus punctatus is associated with low temperature (-12°C) Induced ~mmunosuppress~on and ~nvaslon by a ubiqu~tous opportunistic water mold, Identified as a S a p~o l e g n~a sp In t h~s study attempts were made to identify antiinicrob~als/chemlcals w h~c h may (1) be effect~ve for the therapeut~c treatment of xvlnter saprolegniosis and (2) prophylact~cally control water concentrations of Saprolegn~a and hence prevent the onset of dlsease under laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 9 publications
(12 reference statements)
0
12
0
3
Order By: Relevance
“…The intricate associations of such factors reflect the difficulty of establishing controlled infection studies to observe such opportunistic fungal infections and any benefit this potential probiotic might deliver. Existing methods for inducing saprolegniosis in fish (Hatai & Hoshiai 1993; Bly, Quiniou, Lawson & Clem 1996; Howe & Stehly 1998) use a combination of stresses suitable for studying the pathogenesis of the disease. These are, however, likely to be inapplicable for probiotic investigations, where a constant reproducible percentage of infection is required for statistical validity.…”
Section: Discussionmentioning
confidence: 99%
“…The intricate associations of such factors reflect the difficulty of establishing controlled infection studies to observe such opportunistic fungal infections and any benefit this potential probiotic might deliver. Existing methods for inducing saprolegniosis in fish (Hatai & Hoshiai 1993; Bly, Quiniou, Lawson & Clem 1996; Howe & Stehly 1998) use a combination of stresses suitable for studying the pathogenesis of the disease. These are, however, likely to be inapplicable for probiotic investigations, where a constant reproducible percentage of infection is required for statistical validity.…”
Section: Discussionmentioning
confidence: 99%
“…Fajer-Ávila et al (20), surveying the antiparasitic properties of the compound against ectoparasites (among which A. ocellatum) of bullseye puffer fish (Sphoeroides annulatus), reported 4 mg/L as the dose at which the compound had less adverse effects on fish in long-term exposure and reduced the parasite burden on skin and gills after 7 h of treatment. With respect to Saprolegnia, formalin has been effectively employed for egg disinfection in aquaculture to both treat and prevent infection in fish eggs (21). These authors observed that it is capable of inhibiting Saprolegnia cyst germination at a concentration of 250 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Formalin, a solution of 37% formaldehyde, has been effectively employed to prevent (Bly, Quiniou, Lawson, & Clem, ; Schreier, Rach, & Howe, ) and treat (Cline & Post, ; Marking, Rach, & Schreier, ; Walser & Phelps, ) Saprolegnia infection in fish eggs. As a prophylactic measure, it inhibits cyst germination at a concentration of 250 mg/L (Bly et al., ). Daily flushes of formalin with 100, 200 and 400 mg/L increased per cent hatch of channel catfish Ictalurus punctatus eggs in comparison with non‐treated eggs (Walser & Phelps, ).…”
Section: Introductionmentioning
confidence: 99%